Forest reclamation of the postmining dumps. I. Changes in the properties of miocene sediments material = Rekultywacja leśna hałd pokopalnianych. I. Zmiana właściwości gruntu zwałowego pochodzenia mioceńskiego - Drab, Michał; Greinert, Henryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Miocene sediments, collected during brown coal excavation, have generally mechanical composition of loamy sand. The most negative feature of them is a very low pH-value, in a consequence of pyrite-oxidation. 20 years after technical reclamation and dump areas afforestation, a few conclusions about effects of the reclamation have been drawn:
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); miocene sediments; dumps reclamation; forest reclamation; anthropogenic soils